2017
DOI: 10.3390/rs9020103
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Spaceborne and Modelled Surface Soil Moisture Products with Cosmic-Ray Neutron Probes

Abstract: Abstract:The scale difference between point in situ soil moisture measurements and low resolution satellite products limits the quality of any validation efforts in heterogeneous regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
69
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 140 publications
(134 reference statements)
5
69
1
Order By: Relevance
“…Additionally, many key hydrologic processes are extremely difficult to parameterize (e.g., irrigation, dam operation, snow melting, and interception), especially in challenging regions (deserts, pluvial forests, and high altitudes). Therefore, modelled soil moisture data surely represents an important dataset that, however, needs to be used with caution [70,71].…”
Section: Hydrological and Land Surface Modellingmentioning
confidence: 99%
“…Additionally, many key hydrologic processes are extremely difficult to parameterize (e.g., irrigation, dam operation, snow melting, and interception), especially in challenging regions (deserts, pluvial forests, and high altitudes). Therefore, modelled soil moisture data surely represents an important dataset that, however, needs to be used with caution [70,71].…”
Section: Hydrological and Land Surface Modellingmentioning
confidence: 99%
“…The performance of satellite and modeling products was assessed using CRN soil moisture data sets (Kim et al, 2015; Evans et al, 2016; Kędzior and Zawadzki, 2016; Vinodkumar et al, 2017; Montzka et al, 2017). Overall, CRN soil moisture was found to be appropriate for validation and for identifying areas of improvement in the parameterizations and the model for the retrieval algorithms.…”
Section: Status Of the Methodsmentioning
confidence: 99%
“…Montzka et al (2017) identified some challenges in validating satellite‐retrieved soil moisture using CRN detectors. Satellite‐retrieved soil moisture was lower than CRN measurements during periods with considerable amounts of biomass.…”
Section: Challenges and Potential Improvementsmentioning
confidence: 99%
“…Comprising a growing network of more than 200 cosmicray neutron probes at fixed installations across six continents, these data represent a valuable source of independent infor-5 See http://www.nature.com/news/ mobile-phone-signals-bolster-street-level-rain-forecasts-1.21799. mation from which a range of hydrological responses may be inferred or assessed (Jana et al, 2016;Montzka et al, 2017).…”
Section: Signals Of Opportunitymentioning
confidence: 99%